The Role and Clinical Significance of Vitamin D in Chronic Obstructive Pulmonary Disease - Sun M; Qian Y; Cai C; Zhang J; Qi R; Ma H; Ding Q; Wang S; Lv D (International Journal of COPD)
Mengqing Sun, Yang Qian, Chenting Cai, Jiaqian Zhang, Ruonan Qi, Hongying Ma, Qunli Ding, Shanshan Wang, Dan Lv Department of Respiratory and Critical Care Medicine, the First Affiliated Hospital of Ningbo University, Ningbo, Zhejiang Province, People’s Republic of ChinaCorrespondence: Dan Lv, Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital of Ningbo University, No. 59, Liuting Street, Haishu District, Ningbo, Zhejiang Province, People’s Republic of China, Email fylvdan@nbu.edu.cnAbstract: Vitamin D is well known for its role in bones, but it also has a variety of extra-skeletal effects. Vitamin D deficiency is becoming a global health problem. Chronic obstructive pulmonary disease (COPD) is the third leading cause of death in the world, resulting in an enormous medical and economic burden. Accumulating evidence indicates a high prevalence of vitamin D deficiency in patients with COPD, which has emerged as a significant modulator of disease progression. This comprehensive review systematically examines the multifactorial etiology of vitamin D deficiency in COPD, encompassing insufficient sunlight exposure, malnutrition, smoking, comorbidities, and chronic inflammatory states. Clinical observational studies have demonstrated significant associations between vitamin D deficiency and increased exacerbation frequency, accelerated lung function decline, and elevated mortality risk. Mechanistically, we elucidate the pleiotropic effects of vitamin D in COPD pathogenesis, including its anti-inflammatory activity, suppression of oxidative stress, modulation of innate and adaptive immunity, inhibition of hepcidin, and reduction in pulmonary infection risk. Building on current evidence, we critically evaluate the clinical efficacy of various vitamin D supplementation strategies. This review aims to provide clinicians with an evidence-based framework for incorporating vitamin D assessment and supplementation into comprehensive COPD management while also identifying key directions for future research.Keywords: COPD, AECOPD, vitamin D, vitamin D supplement, vitamin D deficiency